Lessons from the field: Supporting infection prevention and control and antimicrobial stewardship in Amman, Jordan - Anita Shallal; Joud Jarrah; Tyler Prentiss; Geehan Suleyman; Michael P. Veve; Ayat Banat; John Zervos; Ayman Bani Mousa; Lama Msadeh; Fatima Mustafa Zerriouh Thneibat; Marcus Zervos; Jamela Al-Raiby; et al. (Elsevier, 2023)
Background: To reduce antimicrobial resistance (AMR), appropriate antimicrobial prescribing is critical. In conjunction with Infection Prevention & Control (IPC) programs, Antimicrobial Stewardship Programs (ASP) have been shown to improve prescribing practices and patient outcomes. Low- and middle-income countries (LMIC) face challenges related to inadequate ASP policies and guidelines at both the national and healthcare facility (HCF) levels. Methods: To address this challenge, the World Health Organization (WHO) created a policy guidance and practical toolkit for implementation of ASPs in LMIC. We utilized this document to support a situational analysis and two-day ASP-focused workshop. In follow-up, we invited these attendees, additional HCF and hospital directors to attend a workshop focused on the benefits of supporting these programs. Results: Over the course of a total three days, we recruited hospital directors, ASP team members, and IPC officers from fifteen different healthcare facilities in Jordan. We describe the courses and coordination, feedback from participants, and lessons learned for future implementation. Conclusions: Future efforts will include more time for panel-type discussion. which will assist in further delineating enablers and barriers. Also planned is a total three-day workshop; with the first two days being with ASP/IPC teams, and the final third day being with hospital directors and leadership. The WHO policy guidance and toolkit are useful tools to address overuse of antimicrobial agents. Strong leadership support is needed for successful implementation of ASP and IPC. Discussions on quality/safety, as well as cost analyses, are important to generate interest of stakeholders.